THE MUSCLES ENERGY TECHNIQUE ISOMETRIC LEBIH MENINGKATKAN FLEKSIBILITAS OTOT HAMSTRING DARI PADA STATIC STRETCHING PADA PEMAIN SEPAK BOLA PHYSIO TEAM FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Palguna, I Made Wahyu; Nurmawan, Sutha; Muliarta, I Made (Majalah Ilmiah Fisioterapi Indonesia; Vol 3 No 3 (2015): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2015.v03.i03.p08)
Football has a high incidence rate of injuries such as hamstring strain. Stretching exercise is an effort done to prevent injury. The purpose of this research is to investigate the effectiveness of muscle energy technique isometric and static stretching in increasing the flexibility of hamstring muscle. This research was experimental research with pre and post test two group design. The research involved 24 samples which were divide into 2 groups. Group 1 was given the isometric muscle energy technique treatment and group 2 was given the static stretching treatment.Mean different of hamstring muscle flexibility and after the treatment in each group was tested using paired sample t-test. Independent t-test obtained a result p = 0.000 (p<0.05 ). It can be concluded that muscle energy technique isometric is more effective than static stretching in increasing the flexibility of hamstring muscles.
Keywords: muscle energy technique isometric, static stretching, flexibility, hamstring.